Feasibility of real-time treatment feedback using novel filter for eliminating therapeutic ultrasound noise with high-speed ultrasonic imaging in ultrasound-guided high-intensity focused ultrasound treatment. (24th June 2016) - Takagi, Ryo; Jimbo, Hayato; Iwasaki, Ryosuke; Tomiyasu, Kentaro; Yoshizawa, Shin; Umemura, Shin-ichiro
Abstract: In the conventional ultrasonic monitoring of high-intensity focused ultrasound (HIFU) treatment, a significant interval between HIFU shots is required when monitoring target tissue to avoid interference between HIFU noise and RF echo signals. In our previous study, a new filtering method to eliminate only HIFU noise while maintaining tissue signals intact was proposed, and it was shown that the thermal coagulation could be detected during simultaneous HIFU irradiation through off-line processing. In this study, the filtering method and a real-time coagulation detection algorithm were implemented in an ultrasound imaging system, whose use for sequential exposure with multiple foci was demonstrated similarly to a commercial HIFU ablation system. The coagulation was automatically detected by the proposed method during real-time simultaneous HIFU irradiation, and the HIFU exposure time was controlled according to the changes in the tissue. The results imply that ultrasonic monitoring with the filtering and detection methods is useful for true real-time detection of changes in the tissue due to thermal coagulation during HIFU exposure.